Investigating methylparaben’s oxidative stress effects on rainbow trout blood, liver, and kidney toxicity - Mert Calisir; Gokhan Nur; Emrah Caylak (Onderstepoort Journal of Veterinary Research)
The widespread use of parabens has led to their accumulation in aquatic environments. This study examined the effects of methylparaben on rainbow trout, dividing 96 fish into control and treatment groups (1 mg/L, 5 mg/L, and 8 mg/L). Results showed dose-dependent weight loss, altered hepatosomatic indices, increased serum urea, uric acid, and Malondialdehyde (MDA) levels, and decreased Glutathione Peroxidase (GSH-Px) activity. Histopathological analysis revealed liver and kidney abnormalities in treated groups, including hepatocyte degeneration, proliferation in the bile duct, glomerular atrophy, reduced haematopoietic tissue, increased melanomacrophage centres, necrosis and fibrosis.